Molecular dynamics simulation and development of a thermostable endoglucanase I from fusarium oxysporum - Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah; Ahmad, Abdul Aziz (2014)
Thermostable enzymes have several benefits in various industrial applications. Cellulase has been used in various industries such as textile, detergent, food and feed, pulp and paper, and recently in bioethanol production. The major aim of this work is to predict the potential site for mutagenesis computationally and produce the mutant experimentally with improved thermal stability properties and characterize the mutant enzyme